Transcriptional pause release is a rate-limiting step for somatic cell reprogramming - Liu, Longqi; Xu, Yan; He, Minghui; Zhang, Meng; Cui, Fenggong; Lu, Leina; Yao, Mingze; Tian, Weihua; Benda, Christina; Zhuang, Qiang; Huang, Zhijian; Li, Wenjuan; et al. (Cell stem cell, 2014)
Reactivation of the pluripotency network during somatic cell reprogramming by exogenous transcription factors involves chromatin remodeling and the recruitment of RNA polymerase II (Pol II) to target loci. Here, we report that Pol II is engaged at pluripotency promoters in reprogramming but remains paused and inefficiently released. We also show that bromodomain-containing protein 4 (BRD4) stimulates productive transcriptional elongation of pluripotency genes by dissociating the pause release factor P-TEFb from an inactive complex containing HEXIM1. Consequently, BRD4 overexpression enhances reprogramming efficiency and HEXIM1 suppresses it, whereas Brd4 and Hexim1 knockdown do the opposite. We further demonstrate that the reprogramming factor KLF4 helps recruit P-TEFb to pluripotency promoters. Our work thus provides a mechanism for explaining the reactivation of pluripotency genes in reprogramming and unveils an unanticipated role for KLF4 in transcriptional pause release.